Efektifitas Edukasi Model Kartu Pintar Deteksi Dini Risiko Preeklamsia (DEDI RAISA) Terhadap Peningkatan Pengetahuan Ibu Hamil - Fitriani Fitriani; Syahruni Syahruni (Direktorat Politeknik Kesehatan Makassar, 2023)
Early detection plays a role in reducing maternal mortality and is very important. Morbidity and mortality of pregnant women can be prevented if pregnant women themselves are able to recognize the danger signs of pregnancy such as preeclampsia and try to seek help in health facilities, appropriate actions can prevent pregnant women from causing maternal death. This study aims to determine the effectiveness of the smart card education model of early detection of preeclampsia risk (dedi raisa) on increasing the knowledge of pregnant women. This study used a